Groundwater pollution from landfill site on pervious sandy soil - a case study of pollution control - Sapari, Nasiman (1987)
The quality of groundwater near the disused landfill site at Bayswater was monitored and found to be contaminated with leachate from the landfill. Control of the leachate flow by recycling the leachate for irrigation water was studied" This method of control is proposed as a suitable and beneficial alternative for the Perth mediterranean climatic conditions. The flow of the leachate followed the pattern of the groundwater flow of the area. It flowed in an unconfined aquifer underlain by an impermeable clay layer. The quality of the water was monitored from etght monitoring bores sunk down to the clay layer over a period of approximately one year. It was found that a considerable amount of nutrients (ammonia-N and soluble phosphate, up to 60 mg/L and 1.4 mg/L respectively) flowed into the Swan river during the few months after the winter rain. Leachate water that flowed into a lake in the middle of the landfill area was used in a leachate irrigation experiment for growing grasses (couch grass), The grass which was irrigated with the leachate grew better than the grass irrigated with mains water. After ten weeks of irrigation, the runners had an average length of 14.4 cm while the average for the control (with normal fertiliser application) was only 5.9 cm. Biomass accumulation in the plots receiving leachate water was more than double the figure for the control plots. Minimum leachate application at the rate of 140%from evaporation rate is considered necessary for the Perth clim.atic conditions. With this rate of application, an area of 32% of the total landfill area is sufficient for leachate control at Bayswater landfill site by land irrigation.